AUGMENTING EFL STUDENTS’ SPEAKING SKILLS THROUGH THE MYSTERY BOX GAME - Nira Erdiana; Masrizal Mahmud; Syarifah Nisa Khaira; Yunisrina Qismullah Yusuf (English Review: Journal of English Education, 2023)
This study examined how employing the Mystery Box game affected tenth-grade students' speaking skills at a senior high school in Lhokseumawe, Aceh, Indonesia. It employed pre-experimental quantitative research. A number of 25 students from class X-3 were purposively chosen as the sample of this study. In collecting the data, the researchers used tests (pre-test and post-test) as the instrument, and the results were analyzed by using statistics. The results showed that the mean scores of the pre-test and post-test were 37.2 and 73.2, respectively. The mean score of the post-test was higher than the mean score of the pre-test, with the T-test value of 4,556, and the critical value in the t-table (0.05) of 1.711. This implies that the t-score is higher than the t-table (t- score = 4.534> t-table = 1.711), and thus the alternative hypothesis (Ha) of this research was accepted and the null hypothesis (Ho) was rejected. In conclusion, teaching English by using the Mystery Box game to improve these EFL students’ speaking skills succeeded. Consequently, the use of this game is among the alternative media to be used by English teachers in augmenting their students’ skills in speaking English. When students achieve the accuracy and mastery of speaking skills, at a later stage, it can help them move to the improvement of other language skills